Cryptococcal Meningitis in a HIV Seronegative Patient: A Rare Complication of Cerebrospinal Fluid Leak Detected with a New Cisternographic Technique - Chukwunonso Chime; Charbel Ishak; Kishore Kumar; Muhammad Kamal; Srinivasan Krishna; Paul Kelly; Sridhar Chilimuri (Case Reports in Infectious Diseases)
Immune deficiency is usually the underlying predisposing factor for cryptococcal meningitis, though there have been case reports of immunocompetent patients presenting with same. The portal of entry for Cryptococcus neoformans is the respiratory tract, and by hematogenous spread, it causes systemic symptoms. The presence of CSF leak is described to have predisposed our immunocompetent patient to infection by this organism possibly through direct spread. The gold standard for diagnosing CSF leak is by cisternography. In this case, we added a technique where nasal gauze is inserted during the procedure and scanned afterwards for dye, thus increasing the confidence of diagnosis of CSF leak through the nares. Prompt diagnosis and treatment is key to prevent adverse outcomes, and we propose that in patients with cryptococcal meningitis without any identifiable risk factor, evaluation for CSF leak should be considered especially with history of head trauma.